Intra-Articular Corticosteroid or Hyaluronic Acid Injections Are Not Associated with Periprosthetic Joint Infection Risk following Total Knee Arthroplasty - Kurtz, Steven M.; Mont, Michael A.; Chen, Antonia F.; Valle, Craig Della; Sodhi, Nipun; Lau, Edmund; Ong, Kevin L. (The Journal of Knee Surgery, 2021)
This study evaluated whether the preoperative use and timing of the use of hyaluronic acid (HA) and/or corticosteroid (CS) injections were associated with an increased risk of periprosthetic joint infections (PJIs) following primary total knee arthroplasty (TKA). We tested the hypothesis that preoperative injection of HA or CS within 3 months prior to primary TKA was associated with an increased risk of PJI by specifically evaluating the association between PJI risk and (1) injection type; (2) timing; (3) patient demographic factors; and (4) surgery-related factors, such as surgeon injection volume, knee arthroscopy (pre- and postoperative), and hospital length of stay. The 5% Medicare part B claims database was queried for patients who received CS and/or HA injections. Cox proportional hazards regressions evaluated the risk of PJIs after TKA, adjusting for patient and clinical factors, as well as propensity scores. The unadjusted incidence of PJI at 2-year post-TKA was 0.75% for the CS group, 0.89% for the HA group, 0.96% for both CS and HA group, and 0.75% for those who did not use HA or CS in the 12 months before TKA. For patients who used HA and/or CS within 3 months prior to TKA, the unadjusted incidence of PJI at 2-year post-TKA was 0.75% for the CS group, 1.07% for the HA group, and 1.00% for both CS and HA group, compared with 0.77% for those who did not use HA or CS. The number of injections performed per year was inconsistently associated with PJI risk. Overall, we found that intra-articular injections given within the 4-month period prior to TKA were not associated with elevated PJI risk (evaluated at 1, 3, 12, and 24 months after the index TKA) within the elderly Medicare patient population.
Keywords: total knee arthroplasty; periprosthetic joint infection; corticosteroid; hyaluronic acid; injections